Field notes contributed by Marion Brewer, May 27, 1982 - Brewer, Marion M.et al (1982)
Field notes were contributed by Marion Brewer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feet/flatbed